Pelatihan Pembuatan Eco-Enzim pada Kelompok Tani di Desa Bobaneigo Madihutu, Kecamatan Jailolo, Selatan Kabupaten Halmahera Barat - Sapsuha, Yusri; Muh. Ade Salim; Nur Sjafani; Suryati Tjokrodiningrat; Hasriani Ishak; Zauza Abdul Latif; Dewi Apriani Aco (Program Studi Kehutanan, Universitas Khairun, 2024)
Training activities on making eco-enzymes have been carried out in Bobaneigo Madihutu Village, South Jailolo District, West Halmahera Regency with the aim of processing organic waste that is no longer used and disturbs the environment into a product that is useful and has economic value. Eco-enzyme is a liquid fermented organic waste which has various functions, including as a floor cleaner, vegetable and fruit cleaner, insect repellent and plant fertilizer. The event was attended by farmer groups and village officials. The activity began with a presentation about eco-enzymes and their benefits for society and the environment. The results of the activity show that the farmer group in Bobaneigo Village, Madihutu District, South Jailolo District, West Halmahera Regency has been able to process organic waste into eco-enzymes, thereby solving the waste problem and turning it into a valuable economic product. because it can be used as organic fertilizer.